Completing second-grade thematic learning: a classroom action research by implementing learning video at Kabulangka - Susyati, Susyati; Kandaga, Thesa (Nashir Al-Kutub Indonesia, 2024)
The action research was motivated by the low level of learning outcomes of second grade students' at SD Negeri Kubulangka, Cukuh Balak Subdistrict. The purpose of this research was to enhance students' learning outcomes by utilizing video media. This research was conducted from October to November 2021 at Second Grade of SD Negeri Kubulangka, Cukuh Balak Subdistrict, Tanggamus Regency. This type of research was Classroom Action Research consisting of 3 cycles, with each cycle comprising 4 stages: Planning, Implementation, Observation, and Reflection. The data collection techniques and tools employed in this research included research instruments such as students' activity data during learning, activities performed by students during learning to assess their motivation level, teachers' performance in teaching, and learning outcomes at the end of each cycle as supporting data. The research findings indicated that the utilization of video media fostered an enjoyable learning atmosphere, leading to increased student learning activities, thereby resulting in enhanced student learning outcomes. From the first cycle to the second cycle, there was an improvement, with 8 students or 38.1% achieving satisfactory grades in the first cycle, while in the second cycle, there was an increase to 15 students or 71.4%, representing a 33.3% improvement. Meanwhile, in the third cycle, the number of students achieving satisfactory grades was 19 or 90.5%, marking a further increase from the second cycle by 4 students or 19.1%. It can be concluded that video media can enhance both the activity and learning outcomes in thematic learning at Second Grade of SD Negeri Kubulangka, Cukuh Balak Subdistrict, Tanggamus Regency.